1996
DOI: 10.1159/000129434
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Pringle Maneuver on Hemodynamics during Laparoscopic Liver Resection in the Pig

Abstract: The Pringle maneuver (PM) is recognized in conventional liver surgery as a method of controlling bleeding. To determine the hemodynamic effects of the PM during pneumoperitoneum (PP) for laparoscopic liver resection, we measured hemodynamic and blood gas changes in 7 healthy pigs. All variables were recorded 5 min before and 10 and 30 min after employing PP or PM and 10 min after discontinuation of PM. After the induction of PP, cardiac index and arterial carbon dioxide tension significantly increased, accompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…High-flow CO 2 insufflator, a high-quality optical system, laparoscopic ultrasonography, Argon Beam Coagulator, endostaplers with vascular cartridges, and a harmonic dissector are the most common tools necessary for laparoscopic liver resections. Despite deleterious effects of pneumoperitoneum associated with the Pringle maneuver in animal models [71,72], the use of this combination was well tolerated in 6% of the patients in the current series, with an occlusion time varying from 20 to 120 minutes. However, it should be noted that portal triad clamping was used in the current series for liver resections, namely segmentectomies and left lateral segmentectomy, for which it should not have been used during an open approach.…”
Section: Discussionmentioning
confidence: 79%
“…High-flow CO 2 insufflator, a high-quality optical system, laparoscopic ultrasonography, Argon Beam Coagulator, endostaplers with vascular cartridges, and a harmonic dissector are the most common tools necessary for laparoscopic liver resections. Despite deleterious effects of pneumoperitoneum associated with the Pringle maneuver in animal models [71,72], the use of this combination was well tolerated in 6% of the patients in the current series, with an occlusion time varying from 20 to 120 minutes. However, it should be noted that portal triad clamping was used in the current series for liver resections, namely segmentectomies and left lateral segmentectomy, for which it should not have been used during an open approach.…”
Section: Discussionmentioning
confidence: 79%
“…In addition, previous clinical and experimental studies have suggested that the CO 2 pneumoperitoneum is associated with impaired portal blood flow and poor hemodynamic tolerance to portal clamping [25][26][27]. Pneumoperitoneum increases mean arterial pressure and systemic vascular resistance and decreases cardiac output, modifications similar to those observed in chronic heart failure [7,28].…”
Section: Discussionmentioning
confidence: 78%
“…Laparoscopic selective inflow occlusion is more difficult than total vascular occlusion, but it avoided complications of ischemial reperfusion injury and gastrointestinal congestion, corresponding with the goal of minimal invasion of laparoscopic surgery [12][13][14][15]. Furthermore, selective inflow occlusion does not require fast liver transection and allows surgeons to take time for meticulous dissection.…”
Section: Discussionmentioning
confidence: 99%